All-in-one filler-elastomer-based high-performance stretchable piezoelectric nanogenerator for kinetic energy harvesting and self-powered motion monitoring. (November 2018) - Chou, Xiujian; Zhu, Jie; Qian, Shuo; Niu, Xushi; Qian, Jichao; Hou, Xiaojuan; Mu, Jiliang; Geng, Wenping; Cho, Jundong; He, Jian; Xue, Chenyang
Abstract: Flexible nanogenerators with advantages of conformal structure and easy assembly have become an appealing research field for wearable electronics recently. Here, an all-in-one filler-elastomer-based high-performance stretchable piezoelectric nanogenerator (SPENG) is reported. By mechanically shearing and uniformly dispersing high weight compositions of PZT particles and Ag-coated glass microspheres fillers into the identical solid state silicone rubber matrixes, the piezoelectric layer and electrode layers are prepared, respectively, and the SPENG can be fabricated in an all-in-one structure with tight adhesion and reliable durability, which is very important to the tension sensing and energy harvesting for the limb motion with large strain and variable degree of freedom. The stretchable energy harvester exhibits excellent output performances (Voc≈20 V, Isc≈0.55μA, 3.93μW/cm 3 ) and can respond to different external stimulations (such as stretched, clustered, folded, twisted, etc.). The SPENG can be not only mounted on a joint to efficiently capture and convert random body kinetic energy into electricity as a power supply for portable electronics, but also used as the self-powered tension and gesture sensors to monitor dynamic motions. This work has demonstrated a great progress in stretchable electronics and energy harvesting technology, which may have important prospects in artificial intelligence and individualized medical care. Graphical abstract: An all-in-one filler-elastomer-based high-performance stretchable piezoelectric nanogenerator (SPENG) is achieved by dispersing high weight compositions of PZT particles and Ag-coated glass microspheres into identical solid state silicone rubber matrix. Considering excellent mechanical and electrical performances, the SPENG can be acted as an energy harvester to convert kinetic energy into electricity and used as a self-powered sensor to monitor dynamic motions. fx1 Highlights: High-performance stretchable piezoelectric nanogenerator is fabricated. by incorporating PZT particles into the solid state silicone rubber. Our output performance is several times higher than previous reported data. The nanogenerator is in an all-in-one structure with reliable durability. Motion monitoring is demonstrated with the nanogenerator as self-powered sensors.